An Islamic Criminal Law Perspective on Child Sexual Exploitation: Analysis of Verdict No. 40/Pid.Sus/2024/PN.SIM - Arif Siregar, Anwar; Sukiati (Al-Risalah, 2025)
This study aims to analyse the decision of the Simalungun District Court Number 40/Pid.Sus/2024/PN.SIM related to cases of sexual exploitation of children from the perspective of Islamic criminal law. In this case, the defendant was only sentenced to two years in prison, despite being proven to have knowingly exploited a minor through a digital application intermediary. This research uses a normative juridical approach by analysing legislation, Islamic criminal law literature, and court decisions. The results show that the verdict does not reflect substantive justice and is not in line with the principles of child protection in Law Number 35 of 2014 and maqāṣid al-sharī'ah. From an Islamic perspective, sexual exploitation of children is a serious offence that requires strict punishment to provide a deterrent effect. This research recommends the need for a fairer and more pro-victim legal approach to ensure optimal protection and benefit of children.